Optimization of wave pattern of corrugation on plates of heat exchanger - Dvořák Václav (MATEC Web of Conferences, 2017)
The article deals with optimization of undulated heat transfer surface of plate heat exchanger. The goal of optimization is not only to increase effectiveness of heat transfer but also to reduce the pressure drop. Using four optimization parameters, the function describing the shape of corrugations is defined and these parameters are optimized. A simple steepest descent gradient method and stochastic Monte Carlo method are used, the optimum shape of the heat exchange surface is searched for four values of the pressure drop. It was found that a simple steepest descent method quickly gets stuck in a local extreme and the resulting configurations were found only by changing the slope of the waves. The stochastic method enables full optimization through the optimization space and find completely different waveforms with similar values of target function. The question, which shape of the waves on the heat transfer surface is the best, is still open.